Helminths Of Antarctic Rockcod Notothenia Coriiceps (Perciformes, Nototheniidae) From The Akademik Vernadsky Station Area (Argentine Islands, West Antarctica): New Data On The Parasite Community - Kuzmina, T. A.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M. (Zoodiversity, 2020)
Kuzmina, T. A., Salganskij, O. O., Lisitsyna, O. I., Korol, E. M. (2020): Helminths Of Antarctic Rockcod Notothenia Coriiceps (Perciformes, Nototheniidae) From The Akademik Vernadsky Station Area (Argentine Islands, West Antarctica): New Data On The Parasite Community. Zoodiversity 54 (2): 99-110, DOI:10.15407/zoo2020.02.099, URL: http://dx.doi.org/10.15407/zoo2020.02.099